2021
DOI: 10.1242/dev.193508
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical modeling of the interaction between yolk utilization and fish growth in zebrafish,Danio rerio

Abstract: Optimal embryonic development plays a major role in the health of an individual beyond the developmental stage. Nutritional perturbation during development is associated with cardiovascular and metabolic disease later in life. With both nutritional uptake and overall growth being risk factors for eventual health, it is necessary to understand not only the behavior of the processes during development but also their interactions. In this study, we used differential equations, image analyses, curve fittings, para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…This latter model consists of a series of ordinary differential equations, based on physiological processes (biometrics, ontogeny) and physicochemical processes at steady state, thus assuming instantaneous chemical equilibrium between the exposure medium and the internal tissues. Although relevant, some important morphological/physiological changes that may interfere with the substance uptake, e.g., resorption of the yolk sac and the presence/absence of the chorion (Hagedorn et al 1997b;Halbach et al 2020;Schwartz et al 2021) are not taken into account while they can greatly influence the toxicokinetics (TK) of xenobiotics (Halbach et al 2020). Therefore, we aimed to refine the existing PBPK model for the zebrafish eleutheroembryo and to assess its relevance, modeling BPA (a widely used environmental pollutant acting as an endocrine disruptor (Beausoleil et al 2018)), and some of its substitutes, bisphenols AF, AP, B, F, and S (Rosenmai et al 2014), which have been shown to elicit similar mode of action as BPA notably on the ER-signaling in zebrafish eleutheroembryo (Le Fol et al 2017a;Pinto et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This latter model consists of a series of ordinary differential equations, based on physiological processes (biometrics, ontogeny) and physicochemical processes at steady state, thus assuming instantaneous chemical equilibrium between the exposure medium and the internal tissues. Although relevant, some important morphological/physiological changes that may interfere with the substance uptake, e.g., resorption of the yolk sac and the presence/absence of the chorion (Hagedorn et al 1997b;Halbach et al 2020;Schwartz et al 2021) are not taken into account while they can greatly influence the toxicokinetics (TK) of xenobiotics (Halbach et al 2020). Therefore, we aimed to refine the existing PBPK model for the zebrafish eleutheroembryo and to assess its relevance, modeling BPA (a widely used environmental pollutant acting as an endocrine disruptor (Beausoleil et al 2018)), and some of its substitutes, bisphenols AF, AP, B, F, and S (Rosenmai et al 2014), which have been shown to elicit similar mode of action as BPA notably on the ER-signaling in zebrafish eleutheroembryo (Le Fol et al 2017a;Pinto et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…By 5 dpf, larvae inflate their swim bladders, exhibit robust swimming behavior, and actively hunt for food. Zebrafish larvae utilize nutrients from their yolks until at least 7 dpf, and it has been shown that feeding can be delayed until 8 dpf without negatively affecting juvenile survival or growth (Hernandez et al, 2018; Lucore & Connaughton, 2021; Schwartz et al, 2021). A previous study examining the effects of feeding on larval swim behavior, visual stimuli avoidance, and inter-fish distance reported significant behavioral differences between fed and unfed fish at 6 and 7 dpf, but no significant effects at 5 dpf (Clift et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Second, we investigated the effects of feeding on larval visuomotor response behavior. Larvae begin hunting for food by 5 dpf yet can survive solely on nutrients from their yolks until at least 7 dpf (Hernandez et al, 2018;Lucore & Connaughton, 2021;Schwartz et al, 2021), making 5-7 dpf a popular development window for experimentation. While it is known that developmental stage can influence the larval visuomotor response (de Esch et al, 2012;Y.…”
Section: Introductionmentioning
confidence: 99%
“…A decrease in body length at 5 dpf was also observed after exposure to 10 µM rosiglitazone and 10 and 20 µM T0070907 (Figure 1G,H). Because fish length and yolk size are strongly and inversely associated (Schwartz et al, 2021), increased yolk size and decreased length are a common co‐occurrence in studies of early MDC exposure (Almond & Trombetta, 2016; Raldúa et al, 2008; Venezia et al, 2021). Specifically, they are commonly attributed to a reduced yolk utilization because this results in less energy available for growth (Raldúa et al, 2008; Sant & Timme‐Laragy, 2018; Venezia et al, 2021).…”
Section: Discussionmentioning
confidence: 99%